ÉduCoP case study: The Community of Practice of learners in Educational Sciences at the University of Liège - Denis, Brigitte; Bomgart, Marie-Laure (Proceedings of the International Conference on Networked Learning, 2012)
The concept of Community of Practice (CoP) takes nowadays a great part in the formal or informal learning domain. In addition, computerised tools are often used to sustain the activities of these communities (Wenger, White & Smith, 2009). The ÉduCoP case study deals with the creation and the animation process of a CoP that was launched in 2010 at the University of Liège. Initiated by a master student in educational sciences, it aims at developing and making durable a community of practice composed of learners in this field and supported by Information and Communication Technologies. This paper presents several actions undertaken to develop this CoP: the analysis of the potential members’ needs, stakes and motivations of students to enrol in this project; the choice of useful and usable technological tools to provide them (here, the eGroupWare platform) and the training sessions linked to its efficient uses; the activities conducted to develop the CoP’s members identity and to lead them to debate about common topics, to produce and share resources. The CoP’s evolution was observed through qualitative and quantitative data collection processes (e.g. interviews about the members’ implication and roles, support from animator, obstacles, feeling to belong to a CoP, analysis of the topics presented in the posted documents and messages, uses of the technological tools, frequency of connection...). The results are discussed here and perspectives are evoked for this CoP. If the actions undertaken show encouraging results, neverthless obstacles to the creation and the evolution of such a CoP have been identified (e.g. lack of technological culture among some members, reluctance to share personal productions). Some perspectives are considered to overcome these problems. Since October 2011, this initiative has been recognised at the institutional level: the university is interested in lessons learned in order to implement CoP into other faculties that would be willing to start networking and create communities of learners or of practice.